Ultra-miniaturized capacitive loaded conformal frequency selective metasurface for S, C, and X band applications - Haider Ali; Laeeq Riaz; Bilal Tariq Malik; Muhammad Farhan Shafique; Slawomir Koziel (Scientific Reports)
Abstract This paper presents a flexible and low-profile frequency selective metasurface (FSMS) resonating at 10 GHz. The proposed FSMS is a single-layer design with stable response under conformal applications. The inter-element capacitance has been enhanced by introducing lumped capacitors. This technique has significantly reduced the size of the unit element (UE) and enabled operation around the 2 GHz frequency band. The proposed capacitive-loaded structure is highly compact with a wideband transmission response featuring 95% fractional bandwidth (1.2 GHz to 3.1 GHz). The proposed FSMS design architecture is easy to reconfigure for any resonant frequency by tuning the inter-element capacitors. Its small size of 5.3 $$×$$ 5.3 $$\hbox {mm}^2$$ enables the design to be used effectively at S, C, and X-band wrapping applications, which is otherwise infeasible with larger UEs. In addition to miniaturization, the design offers high angular stability and polarization insensitivity for different wrapping angles.